Is insurance instability associated with hypertension outcomes and does this vary by race/ethnicity? - Nancy R. Kressin; Norma Terrin; Amresh D. Hanchate; Lori Lyn Price; Alejandro Moreno-Koehler; Amy LeClair; Jillian Suzukida; Sucharita Kher; Karen M. Freund (BMC, 2020)
Abstract Background Stable health insurance is often associated with better chronic disease care and outcomes. Racial/ethnic health disparities in outcomes are prevalent and may be associated with insurance instability, particularly in the context of health insurance reform. Methods We examined whether insurance instability was associated with uncontrolled blood pressure (UBP) and whether this association varied by race/ethnicity. We used a retrospective longitudinal observational cohort study of patients diagnosed with hypertension who obtained care within two health systems in Massachusetts. We measured the UBP, insurance instability, and race of 43,785 adult primary care patients, age 21-64 with visits from 1/2005-12/2013. Results We found higher rates of UBP for blacks and Hispanics at each time point over the entire 9 years. Insurance instability was associated with greater rates of UBP. Always uninsured black patients fared worst, while white and Hispanic patients with consistent public insurance fared best. Conclusions Stable insurance of any type was associated with better hypertension control than no or unstable insurance.